Discriminative validity of summarized hip and knee angular accelerations for lower extremity training load quantification in male soccer players during a standardised training drill - Bastiaansen, B. J. C.; Vegter, R. J. K.; Wilmes, E.; Goedhart, E.; Lemmink, K. A. P. M.; Brink, M. S. (Science and Medicine in Football, 2025)
This study assessed the discriminative validity of summarized hip and knee angular accelerations during a standardized training drill. Twenty-eight soccer players performed a standardized training drill that mimics game demands. Discriminative validity was examined by assessment of between-group differences of summarized preferred kicking leg hip and knee angular accelerations, and Playerload between national and regional soccer players for the full training drill, and parts based on locomotor intensity, or additional pass and jumping header activities. Furthermore, relationships were assessed between the summarized hip and knee angular accelerations and conventional load indicators derived from a local positioning measurement system, such as high-intensity running distance and Playerload. National players had higher summarized hip (Mean difference: 62.7 A.U. ES = 0.77, p = 0.049) and knee (Mean difference: 137.1 A.U. ES = 1.06, p = 0.008) angular accelerations. Significant interaction effects were observed during high-intensity running (Hip: 0.2 A.U./m, ES = 0.98, p = 0.005; Knee: 0.61 A.U./m, ES = 1.52, p < 0.001), and sprinting (Hip: 0.3 A.U./m, ES = 1.01, p < 0.02; Knee: 0.56 A.U./m, ES = 1.57, p < 0.001). Between-group differences were not present for additional passing or jumping header activities. Compared to summarized hip and knee angular accelerations, Playerload had less ability to discriminate between players and activities. Moreover, the lower extremity training load indicators were unrelated to conventional load indicators. Together these results confirm discriminative validity of summarized hip and knee angular acceleration training load indicators during a standardised training drill.